Advances in researches on mobile health technology-based disease management: a rewiew - Meng-ge TIAN; Xiao-xu YIN; Zu-xun LU (Editorial Office of Chinese Journal of Public Health, 2022)
With the popularization of internet technology, mobile health has been developed vigorously, which makes it possible to overcome the limitations of time, space and manpower and to realize the remote management of diseases aftercare. First, this study analyzes the application of mobile health from three aspects including technology sort, management mode and the direction of disease research; then the study introduces the effect of disease management and cost-benefit analysis based on literature evidences and considerations of patients' demand or feedback. With analyses mentioned above, the study put forward some suggestions for improving disease management system in China.